Interactional Organization and Topic Control in Conciliation Hearings - Ladeira, Wânia Terezinha (The ESPecialist, 2011)
We analyse discursive topic in talk-in-interaction within the institutional setting of three conciliation hearings held in a kind of small claims court for consumption conflict resolution. This research is based on Interactional Sociolinguistics and Conversation Analysis theories. The analysis shows that the participants of those meetings have asymmetric rights regarding the choice of discussion topics. Thus, the mediator is the one who has the right to suggest and control the discursive topics of the conversation. This topic control is the most important institutional procedure that can cause a reduction in accusations and adjacent replies. Consequently, the chance of mediators achieving their institutional task of reaching an agreement between parts in conflict is increased.